2017
DOI: 10.14710/jitaa.42.2.66-71
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of growth of two purelines of Padjadjaran female quail aged 0 to 6 weeks

Abstract: A research was conducted at Quail Breeding Centre of Padjadjaran University.  A hundred quails of female black and brown color of each line was observed from hatch to age of six weeks. Four growth models were compared: Gompertz, Logistic, Richards, and MMF. The best fit was measured with Coefficient of determination (R2) and standard error of prediction (se). The results showed that all observed models have high accuracy with R2 ranging from 0.9950 to 0.9988 for black color, and 0.9984 to 0.9992 for brown colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Similarly, Narinc et al (2010) (R 2 : 0,99998; AIC: -2,010; BIC: -2,172) determined the Gompertz is the best for Japanese quails. Also, Anang et al (2017) determined Gompertz model (R 2 : 0,9988 for black, R 2 : 0,9991 for brown) is the best fit for black and brown plumage colored Padjadjaran quails. In constrat, in some studies Weibull model (R 2 : 0,999; MSE: 318,54; AIC: 4717,067) (Raji et (Yavuz et al 2019) were determined as the best model for Japanese quails.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Similarly, Narinc et al (2010) (R 2 : 0,99998; AIC: -2,010; BIC: -2,172) determined the Gompertz is the best for Japanese quails. Also, Anang et al (2017) determined Gompertz model (R 2 : 0,9988 for black, R 2 : 0,9991 for brown) is the best fit for black and brown plumage colored Padjadjaran quails. In constrat, in some studies Weibull model (R 2 : 0,999; MSE: 318,54; AIC: 4717,067) (Raji et (Yavuz et al 2019) were determined as the best model for Japanese quails.…”
Section: Discussionmentioning
confidence: 83%
“…Similar to current study results, Narinc et al (2014) found 233,12 and Uckardes and Narinç (2014) found the parameter β 0 as 242,10. In constrat, with same model Anang et al (2017) were determined that parameter 164.47 for black, 213,43 for brown; Grieser et al (2018) 167,5 for yellow; 179,6 for red plumage colored quails. On the other hand, Santos et al (2018) found the parameter β 0 for meat and laying type Japanese quails as 305 and 159, respectively.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This result is in agreement with the present study. Anang et al (2017) performed Gompertz, Logistic, Richards, and MMF model for describing the growth of black and brown Japanese quail lines. Although the Gompertz model is the most suitable model, other models showed similar results.…”
Section: Resultsmentioning
confidence: 99%
“…The four main growth components are increased muscle weight consisting of proteins and water, increased skeleton size, increased total body fat in adipose tissue, and increased hair, skin, and internal organs. Quail growth is strongly influenced by genetics and the aim of each breeder's selection process, whether for an egg, meat, or both [19].…”
Section: B Body Weight Gainmentioning
confidence: 99%